2016
DOI: 10.1111/jir.12328
|View full text |Cite
|
Sign up to set email alerts
|

Visual–motor integration, visual perception and motor coordination in a population with Williams syndrome and in typically developing children

Abstract: Background Williams syndrome (WS) is characterised by severe deficits in visual–spatial abilities in contrast to relatively well‐developed language abilities. There is very limited knowledge about visual–motor integration (VMI) in people with WS. Method Twenty‐six participants with WS aged 6 to 41 years were assessed with all three tests of the Beery‐VMI test, namely the VMI test, the visual perception test (VP) and the motor coordination test (MC). Their results were compared with those of 154 typically devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Data on visual-motor integration have shown visual-motor skills at borderline level. As far as we know, this is the first study providing this assessment in dup7q11.23 children, differently from WBS, in which visual motor major impairments have been assessed and documented [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Data on visual-motor integration have shown visual-motor skills at borderline level. As far as we know, this is the first study providing this assessment in dup7q11.23 children, differently from WBS, in which visual motor major impairments have been assessed and documented [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…These findings, however, may not be applicable for all populations. Research investigating children between the ages of four and 12 years old with Williams Syndrome and those of typical development concluded that age impacted VMI scores of children who were typically developing, but not children with Williams syndrome [ 47 ]. Overall, these studies illustrate that age may have varying influences on different populations of children.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Two studies included children five years and older [43,44]. Three studies investigated performance of children starting at four years of age [45][46][47]. One study included children as young as three years six months [48].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…At present, there is rare research on the visual‐motor coordination with digitalised equipment [9–12]. For example, David et al .…”
Section: Introductionmentioning
confidence: 99%